2019 International Conference on Document Analysis and Recognition (ICDAR) 2019
DOI: 10.1109/icdar.2019.00055
|View full text |Cite
|
Sign up to set email alerts
|

Efficient, Lexicon-Free OCR using Deep Learning

Abstract: Contrary to popular belief, Optical Character Recognition (OCR) remains a challenging problem when text occurs in unconstrained environments, like natural scenes, due to geometrical distortions, complex backgrounds, and diverse fonts. In this paper, we present a segmentation-free OCR system that combines deep learning methods, synthetic training data generation, and data augmentation techniques. We render synthetic training data using large text corpora and over 2 000 fonts. To simulate text occurring in compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 24 publications
1
20
0
4
Order By: Relevance
“…This ANN contains 7.8×10 5 weights and has been trained on a large amount of purely synthetic data [29]. While the whole training data is not available online, the provided examples and the generation process description show that Tesseract 4.00 can be used for reference [65]. We additionally provide the results of the previous version, i.e., Tesseract OCR 3.05, as, firstly, it allows comparison with earlier studies, and, secondly, it demonstrated competitive results with other methods [61], [62].…”
Section: ) Tesseract Ocrmentioning
confidence: 99%
See 2 more Smart Citations
“…This ANN contains 7.8×10 5 weights and has been trained on a large amount of purely synthetic data [29]. While the whole training data is not available online, the provided examples and the generation process description show that Tesseract 4.00 can be used for reference [65]. We additionally provide the results of the previous version, i.e., Tesseract OCR 3.05, as, firstly, it allows comparison with earlier studies, and, secondly, it demonstrated competitive results with other methods [61], [62].…”
Section: ) Tesseract Ocrmentioning
confidence: 99%
“…2) ABBYY FINEREADER ABBYY FineReader [66] is a state-of-the-art commercial OCR application [61] that is used in both scientific studies [7], [32], [62], [65] and business. In our experiments, we used the latest ABBYY FineReader 15.…”
Section: ) Tesseract Ocrmentioning
confidence: 99%
See 1 more Smart Citation
“…Optical Character Recognition (OCR) is one of the most widely studied problems in the field of pattern recognition and computer vision [18]. Despite being widely studied, OCR remains a challenging problem when used in unconstrained environments like parking areas.…”
Section: Optical Character Recognitionmentioning
confidence: 99%
“…The problem of Optical Character Recognition (OCR) has been the scope of research for many years [1]- [3] due to the need for an efficient method to digitize printed documents, prevent their loss and gradual unavoidable wear, as well as increase their accessibility and portability. The challenges that face Arabic OCR systems stem from the cursive and continuous nature of Arabic scripts.…”
Section: Introductionmentioning
confidence: 99%